Application of Preventive Measures: A comparative legal analysis of the Republic of Uzbekistan and Spain - Kambarova Shahzoda Alisherovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article provides a comparative legal analysis of preventive measures applied in the criminal procedural systems of the Republic of Uzbekistan and Spain and based on the Criminal Procedure Code of the Republic of Uzbekistan and the Spanish Ley de Enjuiciamiento Criminal, the study examines the legal foundations, types, conditions, and purposes of preventive measures. In particular, such measures as detention, house arrest, bail, personal guarantee, judicial supervision, passport confiscation, restraining orders, and electronic monitoring are analyzed. Special attention is paid to the principle of applying detention in Spain only as a “measure of last resort” (ultima ratio) and to mechanisms aimed at protecting human rights and the article also develops proposals for the gradual implementation of advanced Spanish experience into the legislation of Uzbekistan. The research substantiates the necessity of expanding alternative preventive measures, improving electronic monitoring systems, and strengthening mechanisms for the protection of victims.